Burden of disease from breast cancer attributable to smoking and second‐hand smoke exposure in Europe. Issue 9 (2nd May 2020) - Carreras, Giulia; Lachi, Alessio; Boffi, Roberto; Clancy, Luke; Gallus, Silvano; Fernández, Esteve; López, Maria José; Soriano, Joan B.; López Nicolás, Ángel; Semple, Sean; Behrakis, Panagiotis; Gorini, Giuseppe; et al.
Abstract: Smoking and second‐hand smoke (SHS) exposure have been recently linked to a higher risk of breast cancer in women. The aim of this work is to estimate the number of deaths and disability‐adjusted life years (DALYs) from breast cancer attributable to these two risk factors in the European Union (EU‐28) in 2017. The comparative risk assessment method was used. Data on prevalence of smoking and SHS exposure were extracted from the Eurobarometer surveys, relative risks from a recent meta‐analysis, and data on mortality and DALYs from breast cancer were estimated from the Global Burden of Disease, Injuries and Risk Factors Study. In 2017, 82 239 DALYs and 3354 deaths from breast cancer in the EU‐28 could have been avoided by removing exposure to these two risk factors (smoking and SHS exposure). The proportion of DALYs from breast cancer lost respectively from smoking and SHS exposure was 2.6% and 1.0%, although geographically distributed with significant heterogeneity. These results represent the first estimates of breast cancer burden in women attributable to smoking and SHS exposure for the EU‐28. It is important to increase awareness among women, health professionals and wider society of the association between smoking, SHS exposure and breast cancer, a relationship that is not widely recognised or discussed. Abstract : What's new? Smoking and exposure to secondhand smoke are not considered a major risk factor for breast cancer risk in Europe. Here, the authors publish the first analysis estimating how many deaths and years of disability can be attributed to smoking. Using the comparable risk assessment method, they determined that eliminating smoking could have saved 60 733 years of life with disability and 2719 deaths from breast cancer. Given the burden of disease from breast cancer attributable to smoking, it is important to increase awareness among health professionals and public.